Effects of nicotine on porcine pre-pupertal sertoli cells: An in vitro study. (September 2020) - Marinucci, Lorella; Balloni, Stefania; Bellucci, Catia; Lilli, Cinzia; Stabile, Anna Maria; Calvitti, Mario; Aglietti, Maria Chiara; Gambelunghe, Angela; Muzi, Giacomo; Rende, Mario; Luca, Giovanni; Mancuso, Francesca; et al.
Abstract: Smoke components, such as nicotine and its major metabolites, cross the blood–testis barrier and are detectable in the seminal plasma of both active smokers and individuals exposed to cigarette smoke. In vivo studies in a rat model have further demonstrated that nicotine exposure reduces the weight of the testis, as well as the number of spermatocytes and spermatids, and affects the ultrastructure of Sertoli cells (SC) – which serve as sentinels of spermatogenesis - causing intense germ cell sloughing in the tubular lumen that compromises offspring fertility. This study sought to determine the effects of nicotine on the viability and function of purified pig pre-pubertal SC. Nicotine exposure reduced the mRNA expression and protein levels of anti-Mullerian hormone (AMH) and inhibin B and impaired FSH-r sensitivity via the downregulation of FSH-r and aromatase gene expression compared to untreated SC. Overall, our study suggests that nicotine can significantly alter extracellular matrix and tight junction protein gene expression ( e.g., laminin, integrin, and occludin), thus compromising cross-talk between the interstitial and tubular compartments and enhancing blood–testis barrier (BTB) permeability via downregulation of the mitogen-activated protein kinase (MAPK) pathway. These findings further elucidate a potential mechanism of action underlying nicotine exposure's detrimental effects on SC function in vivo. Highlights: Exposure of purified pig prepubertal SC to sub-toxic nicotine concentrations was performed. Inhibin B and anti-Mullerian hormone (AMH) mRNAs and proteins were decreased. A downregulation of FHS-r and aromatase gene expression was observed. An alteration in the synthesis of ECM components and proteins involved in BTB was observed. Nicotine-related sub-toxicity on SC open important issues in its role in male infertility.